Project Shikamana: Baseline Findings From a Community Empowerment–Based Combination HIV Prevention Trial Among Female Sex Workers in Iringa, Tanzania. (1st January 2017) - Kerrigan, Deanna; Mbwambo, Jessie; Likindikoki, Samuel; Beckham, Sarah; Mwampashi, Ard; Shembilu, Catherine; Mantsios, Andrea; Leddy, Anna; Davis, Wendy; Galai, Noya
Abstract : Background: Community empowerment approaches have been found to be effective in responding to HIV among female sex workers (FSWs) in South Asia and Latin America. To date, limited rigorous evaluations of these approaches have been conducted in sub-Saharan Africa. Methods: A phase II community randomized controlled trial is being conducted in Iringa, Tanzania, to evaluate the effectiveness of a community empowerment–based combination HIV prevention model (Project Shikamana) among a stratified sample of HIV-infected and HIV-uninfected FSWs. Cohort members were recruited from entertainment venues across 2 communities in the region using time-location sampling. All study participants gave consent, and were surveyed and screened for HIV at baseline. Primary biological study outcomes are viral suppression among the HIV-infected and remaining free of HIV among HIV-uninfected women. Results: A cohort of 496 FSWs was established and is currently under follow-up. Baseline HIV prevalence was 40.9% (203/496). Among HIV-infected FSWs, 30.5% (62/203) were previously aware of their HIV status; among those who were aware, 69.4% were on antiretroviral therapy (43/62); and for those on antiretroviral therapy, 69.8% (30/43) were virally suppressed. Factors associated with both HIV infection and viral suppression at baseline included community, age, number of clients, and substance use. Amount of money charged per client and having tested for sexually transmitted infection in the past 6 months were protective for HIV infection. Social cohesion among FSWs was protective for viral suppression. Conclusions: Significant gaps exist in HIV service coverage and progress toward reaching the 90-90-90 goals among FSWs in Iringa, Tanzania. Community empowerment approaches hold promise given the high HIV prevalence, limited services and stigma, discrimination, and violence.